Pekerja Perempuan Yang Terikat Perjanjian Kerja Waktu Tertentu Pada Object Vital Nasional - Buwana, Sudibyo Aji Narendra; Sirajuddin, Sirajuddin; Solehoddin, Solehoddin (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
The legal provisions and regulations contained in Law No. 13 of 2003 concerning Employment related to Specific Time Work Agreements (PKWT) can provide protection for workers in existing employment relationships. This is because when the application of the Specific Time Work Agreement (PKWT) system is not in accordance with the provisions and rules in Law No. 13th of 2003 concerning, of course, having an unfavorable impact on employment development, which aims to provide protection and justice for workers and laborers as part of human resource development in Indonesia, Researchers observed a gap between das sein and dass sollen. The formulation of the problem is how is the legal protection of women workers who are bound by PKWT to National Vital Objects in Kolaka Regency. The type of research used by researchers in this study is empirical-juridical. The research approach used is empirical-juridical, which is closely related to the case approach. Sources of legal materials use primary data, namely interviews and observations conducted by researchers by visiting the research site directly. Secondary data uses primary legal materials, namely applicable laws and regulations, secondary legal materials, namely books, journals, and relevant previous research results, as well as tertiary legal materials in the form of websites. Data collection techniques using in-depth interviews and observation All primary and secondary data in this study were collected and analyzed qualitatively. Conclusions are drawn deductively. The results of his research show that there are three legal protections: pre-employment, during employment, and past employment. The conclusion is that it consists of 3 legal protections, namely preventive legal protection for pre-employment (in the form of announcements of job vacancies, selection of prospective workers, Medical Check Up, and placement of workers); legal protection that is repressive during employment (in the form of providing wages based on the Provincial Minimum Wage/UMP, providing additional roster leave money for those who get roster leave rights, and providing annual allowances, granting leave rights in the form of annual leave, long leave, mass/together leave, roster leave and sick leave, special leave rights for women workers namely maternity leave, abortion leave, and menstruation leave, reimbursement for maternity expenses, protection for women workers when working at certain hours, permission to leave work while still receiving wages, protection for safety and health work by providing personal protective equipment, health insurance protection); as well as legal protection that is repressive in nature past employment, (in the form of the right to get BPJS Ketenagakerjaan pension benefits/JP, the right to get BPJS Ketenagakerjaan old age benefits/JHT benefits)